Khảo sát tự đánh giá năng lực giáo dục STEM của giáo viên trung học cơ sở tại thành phố Hà Nội - Phạm, Ngọc Sơn (Tạp chí Giáo dục, 2025)
In the context of general education reform, STEM education is considered an important orientation in developing comprehensive competence for students. To effectively implement STEM education activities depends largely on the professional competence and pedagogical skills of the teaching staff. This study aims to survey the self-assessment of STEM education capacity of secondary school teachers in Hanoi City through a survey of 165 teachers of natural sciences. The survey results show that teachers have a very positive attitude and high motivation towards STEM education, consider this an important field and are ready to implement it in teaching. Teachers have some fairly good STEM teaching skills, but are still weak in some specific skills such as designing interdisciplinary lesson plans, organizing STEM educational activities, applying integrated STEM teaching methods, etc. The results of this survey will contribute to providing a practical basis, helping education managers build teacher training programs, adjust policies and resources appropriately, thereby narrowing the gap between STEM education orientation in theory and practical implementation in schools.